PORSCHE 911 GT3 : ROAD AND TRACK 1999-2024 - Tipler, Johnny (Marlborough, New Zealand : The Crowood Press Ltd., 2024)
One of the most exciting models ever released by Porsche, the first 911 GT3 was introduced in 1999, based on the then-current 996 coupe, suitably modified as a contender in the FIA GT3 championship category. Successive iterations of the 911 GT3 the 997 GT3, 991 GT3 and present-day 992 GT3 were similarly adapted from the contemporary production-line model, with mechanical and aerodynamic upgrades, constructed at the Stuttgart-based company's Zuffenhausen plant, with upgraded performance in RSR, R and Cup versions applied by its nearby Weissach competition department and test track. With over 300 stunning images, most previously unpublished, including professional photos, factory archive pictures and specially commissioned artworks, and featuring several interviews with Porsche heroes intimately concerned with GT3s in build and in competition, this book tells the thrilling story of a masterpiece of design and technology on road and track.
Includes index.
Keywords: Porsche 911 (Automobile); Porsche 911 automobile -- Pictorial works; Pictorial works